2021
DOI: 10.1002/jmv.26618
|View full text |Cite
|
Sign up to set email alerts
|

Intricacies in characterizing positivity in pooled sample testing for SARS‐CoV‐2

Abstract: The unprecedented demand for testing for the ongoing coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 has led to an acute shortage and limited availability of test reagents for which pooling of samples has been recommended in areas with low prevalence. Con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Their study highlighted the importance of catching late amplification to avoid missing positive samples. When carefully reviewing the PCR curves from pooled testing for case 2, we observed late amplification patterns at the end of the reaction for N1, as described by Mohanty et al (64).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Their study highlighted the importance of catching late amplification to avoid missing positive samples. When carefully reviewing the PCR curves from pooled testing for case 2, we observed late amplification patterns at the end of the reaction for N1, as described by Mohanty et al (64).…”
Section: Discussionmentioning
confidence: 54%
“…Their study highlighted the importance of catching late amplification to avoid missing positive samples. When carefully reviewing the PCR curves from pooled testing for case 2, we observed late amplification patterns at the end of the reaction for N1, as described by Mohanty et al(64).We also encountered a relatively high frequency of PCR inhibition in individual tests, defined as Ct values of IC being unmeasurable or above 40, or by no sigmoid PCR amplification pattern. Saliva can contain inhibitors that impair nucleic acid amplification…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Mohanty et al showed that considering late amplification while interpreting the results of pooled samples allowed the identification of additional positives [ 61 ]. They first used criteria for positivity (Ct within 35 with a sigmoid curve) for 4-sample pools, but also included an additional class of ‘probably positive’ (Ct > 35 with non-sigmoid amplification curve, or increased amplification at the end of the reaction).…”
Section: Discussionmentioning
confidence: 99%